Efficient Preparation of 1,3-Diol Derivatives with Three Contiguous Stereocenters by an Enantioselective Direct Aldol–Tishchenko Reaction - Ichibakase, Tomonori; Nakajima, Makoto (Synthesis, 2012)
1,3-Diol derivatives with three contiguous stereocenters were efficiently prepared by an enantioselective direct aldol–Tishchenko reaction catalyzed by dilithium 3,3′-diphenylbinaphtholate. The reactions of acyclic ketones as aldol donors gave 1,2-syn-1,3-anti-diol derivatives, whereas the reactions of cyclic ketones as aldol donors gave 1,2-anti-1,3-anti-diol derivatives. Sequential aldol–aldol–Tishchenko reactions gave a triol derivative with five consecutive chiral centers.
Keywords: aldol reaction; asymmetric catalysis; enantioselectivity; stereoselectivity; tandem reaction